Flexible Cellulose-Based Electrodes: Towards Eco-friendly All-paper Batteries - L. Zolin; M. Destro; D. Curtil; D. Chaussy; N. Penazzi; D. Beneventi; C. Gerbaldi (Chemical Engineering Transactions, 2014)
In the present work an easy paper-making technique is used for the manufacture of low cost and low environmental impact all-paper-based Li-ion cells. The cells are composed of two paper-like electrodes, prepared using micrometric-sized graphite (anode) and LiFePO4 (cathode) as active materials and truly natural microfibrillated cellulose as binder, and paper hand-sheets soaked in a standard liquid electrolyte solution as separator between them. The specific capacity obtained is even superior to that of standard PVdF-binded cell assembled with the same electrodes, and remains stable over prolonged cycling, indicating that the cellulose fibres do not affect the cycling stability. In this study, no organic solvents or synthetic polymer binders are used all along the production of the cell components which, in addition, can be easily re-dispersed in water by simple mechanical stirring as well as common paper handsheets.